Causal relationships between brain and spinal motor neuron excitability during motor imagery: Using NIRS and evoked electromyogram study - Yuki Fukumoto; Marina Todo; Hiroki Bizen; Daisuke Kimura; Toshiaki Suzuki (NeuroImage: Reports)
In this study, we elucidated the neural basis of motor imagery by using a powerful statistical method in addition to simultaneous brain and spinal measurements using NIRS and evoked electromyogram. We instructed the healthy participants to kinesthetic imagine for contracting the left thenar muscle at 50% maximal voluntary contraction. We examined F-waves and oxygenated-hemoglobin (oxy-Hb) levels simultaneously during motor imagery and the resting condition. During motor imagery was increased the oxy-Hb levels of the supplementary motor area, orbitofrontal cortex, frontopolar cortex, and dorsolateral prefrontal cortex, F-wave/M-wave amplitude ratio, and persistence than in the resting condition. However, other regions of interest, except supplementary motor area, did not correlate with spinal motor neuron excitability. We estimated the causal relationship using structural equation modeling for the brain regions and spinal motor neuron excitability that changed during motor imagery. As a clear series of causal factors, the supplementary motor area involved in the adjustment of gain control of spinal motor neuron excitability, and the dorsolateral prefrontal cortex was connected to the supplementary motor area by an indirect pathway through the parietal lobe region. Therefore, supplementary motor area, dorsolateral prefrontal cortex and spinal motor neuron excitability may play an important role in the execution of motor imagery.